TMS320C6713DSP IMPLEMENTATION OF PULSE SHAPING FILTER - Kang, A.S.; Sharma, Vishal (European Scientific Journal, ESJ, 2013)
One of the most challenging issues facing deployment of 3G technology is how to make the network architectures compatible with each other. New signaling techniques are being designed specially to enhance today’s networks, deliver unprecedented functionality for 3G, and successfully derive the future generation of wireless systems, thus delivering immediate and long term benefits to subscribers. With the architecture of each generation of wireless devices addressed in the development of advance technologies, subscribers can easily evolve their systems without additional network modification, significantly reducing cost and implementing time. The next generation systems based on the DS-CDMA, FDMA/TDMA and GSM concepts are projected to provide transmitting high speed data, video and multimedia traffic for both indoor and outdoor systems, new technologies like Wideband Code Division Multiple Access (WCDMA), already in service, are providing users with high data rate services options like they have never experienced previously. The present paper deals with DSP Implementation of pulse shaping filter for wireless communication.